PENGARUH PENGGUNAAN MULTIMEDIA INTERAKTIF BERBASIS CANVA TERHADAP KEMAMPUAN OPERASI HITUNG PENJUMLAHAN DAN PENGURANGAN BILANGAN PECAHAN DI KELAS V SEKOLAH DASAR - Niken Ananda; Destrinelli; Akhmad Faisal Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the effect of using Canva-based interactive multimedia on the ability of addition and subtraction of fractional numbers in grade V of elementary school. This study uses a quantitative approach of the Pre experimental design type. The design used in this study is one group design, where there is only one experimental class. The results of the study showed that there was a significant difference in the average value of the ability of fractional arithmetic operations in the experimental class. This can be seen from the results of the t-test using an independent sample t-test, obtained a t-count value greater than the t-table value, namely 8.472 > 1.708, and a significance value of P-value 0.00 < 0.05. then Ho is accepted. Then based on the effect size test, the Cohens'd value of 2.357 is included in the large effect size criteria d > 0.8. Based on the results of the study, there is an effect of using Canva-based interactive multimedia on the ability of addition and subtraction of fractional numbers in grade V of elementary school. As well as a large influence of the use of Canva-based interactive multimedia on the ability of addition and subtraction of students' arithmetic operations.